Comparison of peri-implant marginal bone level changes between tapered and straight implant designs: 5-year follow-up results - Park, Han; Moon, Ik-Sang; Chung, Chooryung; Shin, Su-Jung; Huh, Jong-Ki; Yun, Jeong-Ho; Lee, Dong-Won (Journal of periodontal & implant science, 2021)
The aim of this study was to compare straight and tapered implant designs in terms of marginal bone loss, the modified plaque index (mPI), and the modified bleeding index (mBI) for 5 years after functional loading. Twelve patients were recruited. Two types of implants were placed adjacent to each other: 1 straight implant and 1 tapered implant. Marginal bone loss, mPI, and mBI were measured every year for 5 years after loading. The straight implants showed 0.2±0.4 mm of marginal bone loss at 5 years after loading, while the tapered implants showed 0.2±0.3 mm of marginal bone loss; this difference was not statistically significant ( 0.833). Our analysis also showed no statistically significant differences in mPI (straight implants: 0.3±0.3 vs. tapered implants: 0.2±0.3; 0.414) or in mBI (straight implants: 0.3±0.4 vs. tapered implants: 0.2±0.3; 0.317) at 5 years after prosthesis delivery. Straight and tapered implants showed no significant differences with respect to marginal bone loss, mPI, and mBI for 5 years after loading.